Differential Diagnosis in Spine Surgery - Koerner, John D; Vaccaro, Alexander R; Kim, Daniel H (New Delhi : Jaypee Brothers Medical Publishers, 2010)
Practical guide to diagnosis of spine related disorders covering both adult and paediatric conditions. Each topic includes typical case presentations and intiial work up. Internationally recognised author team.
Guía práctica para el diagnóstico de trastornos relacionados con la columna vertebral que cubre tanto condiciones pediátricas como de adultos. Cada tema incluye presentaciones de casos típicos y trabajo inicial.
Contents 1. Lower back pain in children and adolescents 2. Lower back pain in adults 3. Arm pain, weakness and numbness 4. Cervical versus shoulder Periscapular pain 5. Groin pain y otros 9 capítulos más .
Keywords: CIRUGÍA DE LA COLUMNA VERTEBRAL; ENFERMEDADES DE LA COLUMNA VERTEBRAL; SPINE SURGERY